Коротке повідомлення щодо поточного статусу й охорони таксонів темнокорих беріз в Україні та пропоновані зміни до наступного видання Червоної книги України - Tarieiev, Andrii; Olshanskyi, Igor (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
Recently in Ukraine, there were many discussions about proposed changes to the next edition of the Red Book of Ukraine. Kingdom Plantae. In this short communication, we clarify one particular aspect within the discussions concerning the proposition to exclude dark-barked birch Betula obscura from the next edition of the Red Book of Ukraine. It is argued by the new research data obtained and published during last years, and which provide evidence that there is no reason to treat B. obscura as a separate species because it represents only one of at least two different dark-barked birch forms of two widely distributed birch species in Ukraine (B. pendula f. obscura and B. pubescens f. sibakademica), respectively. Therefore, the proposition to exclude B. obscura from the next edition of the Red Book of Ukraine is reasonable since it is aimed to protect plants on the species level only.